Microbial Host Interactions and Impaired Wound Healing in Mice and Humans: Defining a Role for BD14 and NOD2 - Williams, Helen; Campbell, Laura; Crompton, Rachel A.; Singh, Gurdeep; McHugh, Brian J.; Davidson, Donald J.; McBain, Andrew J.; Cruickshank, Sheena M.; Hardman, Matthew J. (Journal of investigative dermatology, 2018)
Chronic wounds cause significant patient morbidity and mortality. A key factor in their etiology is microbial infection, yet skin host-microbiota interactions during wound repair remain poorly understood. Microbiome profiles of noninfected human chronic wounds are associated with subsequent healing outcome. Furthermore, poor clinical healing outcome was associated with increased local expression of the pattern recognition receptor NOD2. To investigate NOD2 function in the context of cutaneous healing, we treated mice with the NOD2 ligand muramyl dipeptide and analyzed wound repair parameters and expression of antimicrobial peptides. Muramyl dipeptide treatment of littermate controls significantly delayed wound repair associated with reduced re-epithelialization, heightened inflammation, and up-regulation of murine β-defensins 1, 3, and particularly 14. We postulated that although murine β-defensin 14 might affect local skin microbial communities, it may further affect other healing parameters. Indeed, exogenously administered murine β-defensin 14 directly delayed mouse primary keratinocyte scratch wound closure in vitro. To further explore the role of murine β-defensin 14 in wound repair, we used Defb14–/– mice and showed they had a global delay in healing in vivo, associated with alterations in wound microbiota. Taken together, these studies suggest a key role for NOD2-mediated regulation of local skin microbiota, which in turn affects chronic wound etiology.